Marketplace’s Role Effectiveness in Women in Lamongan City as a Means of Increasing Sales in The New Normal Era - Levia inggrit sayekti; Muhammad Taufik (Fakultas Ekonomi, Universitas Negeri Jakarta, 2021)
As a result of the Covid-19 pandemic, everyone is obliged to follow the rules New Normal, new habits, new routines, keep your distance, don't crowd and of course the effect of the Covid-19 pandemic has a big impact on entrepreneurial actors, the minimum number of buyers who come to shops or trade stalls which causes a decrease in turnover. In the New Normal Era , entrepreneurs are required to think smart and innovative so that their businesses will continue to run and not lose money, one of the solutions for the New Normal Era is to use the Marketplace Platform as a means of selling online such as Shope, Tokopedia, Bukalapak etc. The research was conducted only on women entrepreneurs in the city of Lamongan with the aim of finding Marketplace Platforms which were the most effective in increasing sales in the era New Normal. The research method was carried out by distributing questionnaires and determining the number of respondents used the snowball sampling method with a total of 100 respondents. The results show that the independent variables X1, X2, X3, X4 and X5 are effective as a Marketplace Platform in increasing sales in the New Normal Era, where f-count has a value of 11.335 at the 5% real level, and a significance value of 0.000. Whereas based on the results of the t test X2 (Shope) has a value of 0.587 or 58.7% and X3 (Tokopedia) has a value of 0.309 or 30.9% the coefficient is positive and significant, which can be stated that the variables X2 (Shope) and X3 (Tokopedia) have an effect. on the variable Y1 (Sales Level Effectiveness).